226k views
4 votes
Please help me!!!!!!!!​

Please help me!!!!!!!!​-example-1
User Stevan
by
5.0k points

2 Answers

2 votes

Answer:

Explanation:

Hello, please consider the following.


cos(\theta)=2cos^2((\theta)/(2))-1\\\\=2\left((p+(1)/(p))/(2)\right)^2-1\\\\=(p^2+(1)/(p^2)+2)/(2)-1\\\\=(1)/(2)(p^2+(1)/(p^2))+1-1\\\\=(1)/(2)(p^2+(1)/(p^2))

Thank you

User Ilissa
by
4.6k points
0 votes

Answer:

see explanation

Explanation:

Using the double angle identity for cosine

cos2x = 2cos²x - 1

Given

cos(
(0)/(2) ) =
(1)/(2)( p +
(1)/(p) ) , then

cosΘ = 2[
(1)/(2)(p +
(1)/(p) ) ]² - 1

= 2 [
(1)/(4)(p² + 2 +
(1)/(p^(2) ) ) ] - 1 ← distribute by 2

=
(1)/(2)(p² + 2 +
(1)/(p^(2) ) ) - 1 ← distribute by
(1)/(2)

=
(1)/(2) p² + 1 +
(1)/(2p^2) - 1

=
(1)/(2) p² +
(1)/(2p^2) ← factor out
(1)/(2) from each term

=
(1)/(2) ( p² +
(1)/(p^(2) ) ) ← as required

User Sultana
by
4.8k points